THE CAUSES OF KNEE JOINT ARTHRITIS AND PHYSICAL EDUCATION (IN THE CASE OF FOOTBALL PLAYERS) TO TREAT IT USING SPECIAL EXERCISES - Valiyev Farrux Nig'matjonovich (Web of Journals Publishing, 2024)
In this article, we will look at the causes of osteoarthritis of the knee joints and explore the role of specific exercises in its treatment. We look at how targeted exercise can benefit people with osteoarthritis, and offer a non-invasive and holistic approach to managing this condition.
Keywords: knee joints, arthrosis, exercises, injuries, surgery, genetic predisposition, osteoarthritis.